Studi Efisiensi Desain Jembatan Beton Prategang dengan Variasi Tipe I-Girder - Bernardinus Herbudiman; Badriana Nuranita; Sandhi Maulana Ivan Putra (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
The prestressed concrete type I (PC-I) girder is widely used in Indonesia’s flyovers due to its strength and construction efficiency. This paper deals with a case study of the Northern Ring Road Flyover structure in Tasikmalaya. The research is focused on stress and deflection ratios of a range of PC-I girder variations, including the existing girder, a smaller girder with more tendons, and a larger girder with fewer tendons. The loading standard follows SNI 1725:2016, while prestressing and capacity analysis refer to AASHTO LRFD Bridge Design Specifications. Result indicated that the H-170 PC-I girder with 3 tendons provides the most efficient design, with a top fiber stress ratio 0.86 and a deflection ratio 0.27 under permanent and live loads, with a total prestress loss of 19.6%.